Immunophenotyping of palatine tonsils in children with OSAS versus recurrent tonsillitis - Tiago Chantre; Juliana Gonçalves; Sofia A. Cerqueira; João Nascimento; Helena Soares; Inês Alpoim Moreira; Mafalda Barroso; Herédio Sousa (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Introduction - Obstructive Sleep Apnea Syndrome (OSAS) and Recurrent Tonsillitis (RA) are the main indications for performing tonsillectomy in children. Despite the growing knowledge in tissue immunology of palatine tonsils, the pathophysiology that leads to the development of OSAS or RA is not fully known.